Elucidating the role of baicalein-enriched fraction to modulate ischemic stroke recovery in rat model - Othman, Farah Amna (2023)
Ischemic stroke is presently the top two leading causes of mortality and long-term adult disability worldwide. Up to date, recombinant tissue plasminogen activator (rtPA) is the one and only approved drug for ischemic stroke therapy. The situation is even worse when this standard therapy has very narrow therapeutic window (~3-4.5 hours) and dentrimental side effects if administered beyond the golden hour. Therefore, natural medicinal plants-based therapy with low side effect and high bioavaibility has emerged as a promising alternative for ischemic stroke. This study assessed the therapeutic potential of baicalein-enriched fraction (BEF), a neuroprotective constituent extracted from the leaves of medicinal plant known as Oroxylum indicum. Prior to any in vivo study using natural botanical extracts or fractions, it is crucial to validate their safety profiles and efficacy through comprehensive toxicological assessments. In this study, the preclinical acute and subacute neurotoxicology assessment of BEF was evaluated based on the Guidelines 420 and 424 set in Organisation for Economic Co-operation and Development (OECD). It was found that the half lethal dose (LD50) of BEF was more than 2000 mg/kg, with no treatment-related toxicity behaviour or neurotoxicity impairments, no alteration in haematological, biochemical and histopathological assessments in both acute and subacute neurotoxicity study. Taking all results together, it was clear that the BEF was safe to be consumed orally and had potential to be developed as an oral drug for ischemic stroke treatment. Thus, 50 mg/kg BEF was orally administered to Sprague Dawley (SD) rats (n=5) for 4 days before the induction of ischemic stroke using endothelin 1 (ET-1). It was found the consumption of BEF pre-ischemic stroke induction could significantly confer protection to the brain tissue against the ischemic injury, shown by the significantly improved neurological deficits, lower brain infarct volume and lower histological score of neuronal degradation in BEF-treated group, compared to the non-treated group. In addition, this study also evaluated the potential of BEF as preconditioning agent to confer protection to neural stem cells (NSCs) against ischemic conditions before transplantation into ischemic stroke rat models for treatment. The results revealed that the experimental rats treated with NSCs preconditioned with BEF at 3.125 μg/mL for 48 hours not only showed significantly decreased brain infarct volume, neuronal degradation and inflammatory cells infiltration, they also showed significantly increased blood vessel density and improved neurological behavioral function as fast as just 24 hours after the treatment, compared to rats treated with non-preconditioned NSCs and non-treated control group. Furthermore, the expression for angiogenic (ANGPT1), anti-oxidant (SOD2), anti-inflammation (IL-1Rn) and neuroprotective (JAKMIP1, STAT6, NGF, NFKβ) genes also significantly increased in the rat treated with BEF-preconditioned NSCs. In conclusion, BEF is a potential drug with neuroprotective and preconditioning effects that could be applied to enhance clinical treatments of ischemic stroke in future.